Modulus of Elasticity of Lightweight Concrete Containing Different Ratios of PET as an Aggregate and Fiber - Taghreed Khaleefa MOHAMMED ALI (Journal of Materials and Engineering Structures, 2018)
In this paper, the modulus of elasticity of lightweight concrete contains polyethylene terephthalate (PET) as fine, coarse aggregate and fiber was estimated by using experimental data from different literatures. The ratios of PET fiber range from 0.5% -1.5%. The modulus of elasticity increased by 8% for 0.5% PET fiber, and decreased by 45% when the concrete contains 1.5% PET fiber. The replacement of the fine or the coarse aggregate by using PET varies between 2.0% - 100%, and this caused decreasing the modulus of elasticity within range 1%-79%. This decreasing effected by shape and size of PET particles, strength of concrete, using of fly ash or silica fume, type of curing and ratio of aggregate to cement. More than 160 data sets, obtained by many investigators using various materials, have been collected and analyzed statistically to introduce the new formula of calculating the modulus of elasticity of concrete contained PET. The compressive strengths of the considered concretes range from 8.1 to 54 MPa. The modulus of elasticity of collected data range from 5.9 to 49 GPa. As a result, a practical equation, which is taken into consideration the ratio of PET as an aggregate or fiber, is proposed.